2008
DOI: 10.1016/j.pneurobio.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin: Elucidating new cellular targets that broaden therapeutic strategies

Abstract: Given that erythropoietin (EPO) is no longer believed to have exclusive biological activity in the hematopoietic system, EPO is now considered to have applicability in a variety of nervous system disorders that can overlap with vascular disease, metabolic impairments, and immune system function. As a result, EPO may offer efficacy for a broad number of disorders that involve Alzheimer's disease, cardiac insufficiency, stroke, trauma, and diabetic complications. During a number of clinical conditions, EPO is ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
155
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(159 citation statements)
references
References 362 publications
1
155
0
1
Order By: Relevance
“…Although EPO was believed to be produced only in the kidney and liver, Tan and colleagues 28 showed in 1992 that other organs, including the brain, produced this cytokine in response to hypoxic-ischemic stress. This finding paved the way for a plethora of studies that increasingly confirmed a number of interrelated functional roles for EPO in the mammalian brain, some of which form the basis for the studies by Mazur and colleagues 18 reported in this issue of Journal of Neurosurgery: Pediatrics.It is now appreciated that endogenously produced EPO reduces the extent of apoptotic injury following ischemia, trauma, and other insults, 9,17,23 and astrocytes may be the primary cell type responsible for this production.3 However, all resident brain cells (neurons, astrocytes, microglia, and endothelial cells) express one or more EPO receptors (EPORs). 17 Erythropoietin and EPORs play important roles in brain development.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Although EPO was believed to be produced only in the kidney and liver, Tan and colleagues 28 showed in 1992 that other organs, including the brain, produced this cytokine in response to hypoxic-ischemic stress. This finding paved the way for a plethora of studies that increasingly confirmed a number of interrelated functional roles for EPO in the mammalian brain, some of which form the basis for the studies by Mazur and colleagues 18 reported in this issue of Journal of Neurosurgery: Pediatrics.It is now appreciated that endogenously produced EPO reduces the extent of apoptotic injury following ischemia, trauma, and other insults, 9,17,23 and astrocytes may be the primary cell type responsible for this production.3 However, all resident brain cells (neurons, astrocytes, microglia, and endothelial cells) express one or more EPO receptors (EPORs). 17 Erythropoietin and EPORs play important roles in brain development.…”
mentioning
confidence: 99%
“…17 Generally speaking, the expression of both EPO and EPORs in adults are upregulated in a temporally distinct, cell-specific manner 1,24 in response to many different stimuli, secondary to the stabilization of one or more isoforms of hypoxia-inducible factor, a transcription factor family responsible for inducing the expression of hundreds of survival-enhancing genes.…”
mentioning
confidence: 99%
See 3 more Smart Citations